Sub-Lethal Dose of Shiga Toxin 2 from Enterohemorrhagic Escherichia coli Affects Balance and Cerebellar Cytoarchitecture - D’Alessio, Luciana; Pinto, Alipio; Cangelosi, Adriana; Geoghegan, Patricia A.; Tironi-Farinati, Carla; Brener, Gabriela J.; Goldstein, Jorge (Frontiers in Microbiology, 2016)
Shiga toxin producing Escherichia coli may damage the central nervous system before or concomitantly to manifested hemolytic uremic syndrome symptoms. The cerebellum is frequently damaged during this syndrome, however the deleterious effects of Shiga toxin 2 has never been integrally reported by ultrastructural, physiological and behavioral means. The aim of this study was to determine the cerebellar compromise after intravenous administration of a sub-lethal dose of Shiga toxin 2 by measuring the cerebellar blood brain barrier permeability, behavioral task of cerebellar functionality (inclined plane test), and ultrastructural analysis (transmission electron microscope). Intravenous administration of vehicle (control group), sub-lethal dose of 0.5 ηg and 1 ηg of Stx2 per mouse were tested for behavioral and ultrastructural studies. A set of three independent experiments were performed for each study (n=6). Blood–Brain Barrier resulted damaged and consequently its permeability was significantly increased. Lower scores obtained in the inclined plane task denoted poor cerebellar functionality in comparison to their controls. The most significant lower score was obtained after 5 days of 1ηg of toxin administration. Transmission electron microscope micrographs from the Stx2-treated groups showed neurons with a progressive neurodegenerative condition in a dose dependent manner. As sub-lethal intravenous Shiga toxin 2 altered the blood brain barrier permeability in the cerebellum the toxin penetrated the cerebellar parenchyma and produced cell damaged with significant functional implications in the test balance.